Organophosphate Pesticide-induced Cytotoxicity in Rat Peripheral Blood Lymphocytes and Ameliorating Effect of Quercetin - Bhadauriya, Mradu; Dubey, Preety; Srivastava, Nalini (International Journal of Scientific Research in Biological Sciences, 2021)
Organophosphate pesticides (OP) are the most extensively used chemicals all over the world and therefore, responsible for most of the human poisoning cases. Present study is carried out to evaluate the in vitro toxicity of quinalphos (QNP) and chlorpyrifos (CPF), the two commonly used OP pesticides, using rat peripheral lymphocytes, and protective effects of a natural flavanoid, quercetin. Results showed dose-dependent and exposure-time dependent cytotoxicity of both QNP and CPF, estimated by MTT assay and lactate dehydrogenase release in culture medium. The pesticides also showed dose-dependent decrease in the levels of ATP in lymphocytes. The results clearly showed compromised membrane integrity leading to cell death by lysis on exposure with QNP or CPF. The anticholinesterase activity of QNP and CPF were evident from the dose-dependent inhibition of acetylcholinesterase (AChE) activity in cultured rat lymphocytes. Quercetin, a well-known flavanoid with antioxidant activity, when given along with the QNP and CPF, resulted in decreased toxicity of both the pesticides. Quercetin co-treatment therefore, offered partial protection against OP pesticide induced toxicity.